Rapid Characterization of Complex Killer Cell Immunoglobulin-Like Receptor (KIR) Regions Using Cas9 Enrichment and Nanopore Sequencing - Bruijnesteijn, Jesse; van der Wiel, Marit; de Groot, Natasja G.; Bontrop, Ronald E. (Frontiers in Immunology, 2021)
Long-read sequencing approaches have considerably improved the quality and contiguity of genome assemblies. Such platforms bear the potential to resolve even extremely complex regions, such as multigenic immune families and repetitive stretches of DNA. Deep sequencing coverage, however, is required to overcome low nucleotide accuracy, especially in regions with high homopolymer density, copy number variation, and sequence similarity, such as the MHC and KIR gene clusters of the immune system. Therefore, we have adapted a targeted enrichment protocol in combination with long-read sequencing to efficiently annotate complex KIR gene regions. Using Cas9 endonuclease activity, segments of the KIR gene cluster were enriched and sequenced on an Oxford Nanopore Technologies platform. This provided sufficient coverage to accurately resolve and phase highly complex KIR haplotypes. Our strategy eliminates PCR-induced amplification errors, facilitates rapid characterization of large and complex multigenic regions, including its epigenetic footprint, and is applicable in multiple species, even in the absence of a reference genome.